Quantum Dynamics of Nitrogen Vacancy center spin coupled with nonlinear nanomechanical resonator - Singh, Abhishek Kumar (IIT(BHU), 2022)
Abstract is available in the attachment
This Thesis Submitted by PHD Scholar IIT (BHU), Varanasi. supervised by Prof. Sunil Kumar Mishra.
Keywords: Quantum; Dynamics; Nanomechanical; Resonator; Nitrogen